Tyranny of the Bottom Line Performance: Tinjauan Kritis terhadap Konsep Kinerja Akuntansi - Alimuddin, Alimuddin (Universitas Brawijaya, Indonesia, 2008)
An enterprise was firsly built in order to satisfy public interest and not aimed at satisfying investor/owner interest. This orientation has been changing in concommitant with the increase of capitalism economy system and agency theory that encorage the corporation to improve financial performance to, lately, meet owner interest. Measurement of its performance already changed to financial performance judgement, in form of profit maximation, ROI/ROA, EVA, and balanced scorecard also. Such financial judgement was in fact banned and recommended to increase its social responsibility more. At the same time, Islamic law (syariah) offered performance judgement and its encouragement with religious spirits.